RETRACTED: Preparation and Analysis of Structured Color Janus Droplets Based on Microfluidic 3D Droplet Printing - Chuang Wu; Hanqi Jia; Haithm Yahya Mohammed Almuaalemi; A. S. M. Muhtasim Fuad Sohan; Binfeng Yin (Micromachines)
The microfluidic technique for the three-dimensional (3D) printing of Janus droplets offers precise control over their size, orientation, and positioning. The proposed approach investigates the impact of variables such as the volume ratio of the oil phase, droplet size, and the ratio of nonionic surfactants on the dimensions of the structured color apertures of Janus droplets. The findings reveal that structured color apertures modulate accurately. Furthermore, fabricating color patterns facilitates cat, fish, and various other specific shapes using structured color Janus droplets. The color patterns exhibit temperature-sensitive properties, enabling them to transition between display and concealed states. Herein, the adopted microfluidic technique creates Janus droplets with customizable characteristics and uniform size, solving orientation as well as space arrangement problems. This approach holds promising applications for optical devices, sensors, and biomimetic systems.